Myth-busting in an Aboriginal pre-university bridging program: Embedding transformative learning pedagogy - Bennett, Rebecca; Strehlow, Karin; Hill, Braden (The Australian Journal of Indigenous Education, 2022)
Pre-university bridging programs can address the significant under-representation of Indigenous students in Australian universities by providing culturally supported alternative pathways into undergraduate study. However, successful completion of bridging programs does not always correlate with university enrolment for Indigenous students. This paper offers a pedagogical rationale for an Indigenous bridging program that aims to address this discrepancy. The program curriculum challenges deficit myths about Aboriginal and Torres Strait Islander Australians and education, while developing foundational academic skills for university study. Leveraging Transformative Learning and Cultural Interface theories, the program aims to empower students with the opportunity to develop their own narratives about Indigeneity and university, free from deficit stereotypes. Since implementation of this myth-busting pedagogy, Indigenous student records indicate marked improvement in bridging program pass rates and in transitions into undergraduate study. Additionally, enrolments into Science, Technology, Engineering and Maths (STEM) tripled. Students’ weekly reflections, collected over seven iterations of the course, suggest that the transformative pedagogy developed students’ self-awareness, self-efficacy, self-confidence and sense of belonging at university.